2019
DOI: 10.1002/jclp.22855
|View full text |Cite
|
Sign up to set email alerts
|

Somatic burden and perceived cognitive problems in trauma‐exposed adults with posttraumatic stress symptoms or pain

Abstract: Objective Posttraumatic stress disorder (PTSD) is associated with somatic and cognitive changes, which may be magnified when accompanied by persistent pain. The mechanisms of somatic sensation processing may extend to cognitive symptoms, revealing a potential generalization of impairment across cognitive and somatic domains in PTSD. We hypothesized that somatic burden would mediate relationships between PTSD, pain, and perceived cognitive impairment. Methods Two samples—360 trauma‐exposed college students and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Anxiety, depression and PTSD is associated with somatic symptoms (Haug, Mykletun & Dahl, 2004;Bartel et al, 2020). It is thought that the somatic sensory processing mechanism extends to cognitive symptoms and reveals a potential generalization of the impairment in the cognitive and somatic domains in PTSD [31].In line with this, it is seen that 'negative alterations in cognitions and mood' are high in severe somatic distress in PTSD symptomology like other symptomatologies in this study.…”
Section: Multiple Linear Regression Analyses For Somatic Distresssupporting
confidence: 80%
“…Anxiety, depression and PTSD is associated with somatic symptoms (Haug, Mykletun & Dahl, 2004;Bartel et al, 2020). It is thought that the somatic sensory processing mechanism extends to cognitive symptoms and reveals a potential generalization of the impairment in the cognitive and somatic domains in PTSD [31].In line with this, it is seen that 'negative alterations in cognitions and mood' are high in severe somatic distress in PTSD symptomology like other symptomatologies in this study.…”
Section: Multiple Linear Regression Analyses For Somatic Distresssupporting
confidence: 80%
“…Higher somatic burden (i.e., the cumulative experience of and distress related to somatic symptoms such as pain) is significantly associated with depression and anxiety (Gierk et al, 2014). In a recent study, somatic burden was found to partially mediate the relationship between PTSD and perception of cognitive problems; whereas, no direct effect was found between pain severity and perception of cognitive problems (Bartel et al, 2019). It seems plausible that there is a more complexinteraction occurring between pain severity, the somatic burden of pain, accompanying psychological distress (i.e., anxiety and depression), and OGM which is worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, subjects with PTSD showed more severe chronic pain and this latter correlated with post-traumatic stress symptoms. 54,55 Pain and PTSD are associated with similar neurobiological abnormalities, 56,57 as hyperarousal, 58 dysregulations in stress responses, 59 and in pain modulation. 60 PTSD subjects show an intense and widespread chronic pain and a peculiar sensory profile of hyposensitivity to pain, related to increased dissociation, accompanied by hyperreactivity to suprathreshold noxious stimuli, linked to increased anxiety sensitivity.…”
Section: Discussionmentioning
confidence: 99%